Komunikasi Terapeutik Keluarga Muslim di Bandung: Analisis Fungsi Narasi dan Keteladanan - Noviar, Tri Nur Aini; Chatamallah, Maman; Zulfebriges, Zulfebriges; Iskandar, Doddy (Jurnal Komunikasi Islam, 2021)
Therapeutic communication basically aims to develop oneself and state of mind in order to lead to be more positive. This article is a qualitative research report that examines the role of narrative interaction and goodly model of parents as a form of therapeutic communication within Muslim families. The results have showed that storytelling and exemplary techniques in the sense of pleasant interpersonal communication can be used to foster the healing process and create a healthy lifestyle in the family. These techniques can keep children in a more positive state of mind, including through giving suggestions and strengthening Islamic spiritual values. This can be conducted by a clear understanding regarding the character of the child’s communication, followed by seting the narrative technique and goodly model that parents must take.